Natural User interface using Microsoft Kinect and HTK - Kumar, Umesh (My University, 2015)
Now a days, the NUI is already popular in the form of multi-touch screens, which found its place in portable devices like Mobiles, Laptops, to Selecting objects, handling with multimedia and images with the help of multi touch interface. The Touch less NUI converts the body Gesture to command for Computer. Nowadays, everybody is using mobile phone and computer as a very important gadget in their life. But there are some physically challenged people who are blind and the use of mobile phone or computer like device is very difficult for them. So, There is an immense need of a system which works on body gesture or sign of sign language and speech as input, so there is the need to develop Touch less NUI which can recognize the body gesture and speech command, In order to solve the problem statement, objectives have been framed for this thesis work. And use the Microsoft Kinect Sensor and SDK V2 and HTK. Which can recognize the object, location of object, motion of object, shape of object human body. HTK provides the interface to implement the HMM model which has been used to implement Speech recognizer system. Developed Touch lees NUI provide interface to control the cursor and click operation just by waving hand gesture and Speech command.
ME, CSED
Keywords: Kinect; Natural User InterFace; HTK; Hand Gesture; CSED